(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The rapid development of information technology has brought significant changes in social life, particularly among students. One form of this change is the increasingly intensive use of social media in daily life, which impacts the morals among individuals. This study aims to investigate the use of social media and its effects on the morals of fellow humans among students of class X.E3 at SMA Negeri 7 Padang. This research employs a qualitative research method with a case study approach through observation, interviews, and documentation techniques. It involves nine students and one guidance counselor as informants. Data was obtained through interviews and analyzed through the stages of data collection, reduction, presentation, and drawing conclusions. The research results indicate that the use of social media is more focused on entertainment rather than as a learning tool, and the social media that is most frequently used by students is TikTok and Instagram with an average usage time of between 3 to 5 hours per day. The positive impacts of social media use are fivefold, including increasing tolerant attitudes, fostering empathy, facilitating communication, encouraging social participation, and spreading useful information. There are also five negative impacts which include disrespectful behavior, a decrease in empathy, disrespect towards parents and teachers, the emergence of envy, and a decline in the quality of direct social interactions.